Synthesis and biological evaluation of PSMA-targeting paclitaxel conjugates. Issue 16 (15th August 2019) - Machulkin, Alexey E.; Skvortsov, Dmitry A.; Ivanenkov, Yan A.; Ber, Anton P.; Kavalchuk, Mikhail V.; Aladinskaya, Anastasia V.; Uspenskaya, Anastasia A.; Shafikov, Radik R.; Plotnikova, Ekaterina A.; Yakubovskaya, Raisa I.; Nimenko, Ekaterina A.; Zyk, Nikolay U.; et al.
Graphical abstract: Abstract: Prostate cancer (PC) is the second most commonly occurring cancer in men. Conventional chemotherapy has wide variety of disadvantages such as high systemic toxicity and low selectivity. Targeted drug delivery is a promising approach to decrease side effects of therapy. Prostate specific membrane antigen (PSMA) is overexpressed in prostate cancer cells while low level of expression is observed in normal cells. In this study we describe the development of Glu-urea-Lys based PSMA-targeting conjugates with paclitaxel. A series of new PSMA targeting conjugates with paclitaxel was designed and synthesized. The cytotoxicity of conjugates was evaluated against prostate (LNCaP, 22Rv1 and PC-3) and non-prostate (Hek293T, VA13, A549 and MCF-7) cell lines. The most promising conjugate 21 was examined in vivo using 22Rv1 xenograft mice model. It demonstrated good efficiency comparable with paclitaxel, while reduced toxicity. 3D molecular docking study was also performed to understand underlying mechanism of binding and further optimization of the linker substructure and conjugates structure for improving the target affinity. These conjugates may be useful for further design of novel PSMA targeting delivery systems for PC.